The role of apprenticeships in the future of vocational education in Europe - Grollmann, Philipp [Verfasser]; Markowitsch, Jörg [Verfasser] (My University, 2019)
"We present possible futures of apprenticeships in Europe by using a two-dimensional model that has been developed recently to describe long-term changes in VET. Based on this model we sketch the future concept and role of apprenticeship within the broader context of VET: Apprenticeship as (1) stigma, (2) integrated apprenticeship and apprenticeship as (3) label." (authors' abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2 Europa; Berufsbildungssystem; Zukunftsperspektive; Szenario; Europa; Internationaler Vergleich